Overview of Big Data platforms - Gabriel Wróbel; Maciej Daniel Wikira (Journal of Computer Sciences Institute, 2019)
The primary purpose of this paper is to present and provide main advantages and disadvantages of most popular big data platforms as well as their comparison in terms of ease of installation, work, performance and price, in order to find the most suitable solution to work with big sets of data. Nowadays, the data is largely analyzed by scientists not related to IT, so the ease of use and presentation of data is extremely important. The purpose of the assessment was to indicate the best IT tool for analyzing data from the point of view of a young analyst or scientist graduating and entering the labor market.